The war on Gaza and its impact on public health: challenges and pathways to recovery - Al Bakri, Deema; Khader, Yousef; Khatib, Rana; Al-Hammouri, Fawzi; Aabed, Mousa; Abed, Yehia; Zureikat, Yousef; Lattouf, Omar; Shatat, Ahmad; Husseini, Abdullatif; Al Nsour, Mohannad; Bashier, Haitham (Frontiers in Public Health, 2025)
The ongoing humanitarian crisis in Gaza has created an unprecedented public health emergency, accompanied by the destruction of critical healthcare infrastructure, widespread shortages of essential resources, and the displacement of millions of the Gazan population. The escalation of conflict since October 2023 has severely strained Gaza’s already fragile health system. As a result, there has been an alarming increase in communicable diseases, malnutrition, and mental health challenges. Furthermore, healthcare facilities and healthcare workers have been systematically targeted, which has led the primary and emergency healthcare services to be on the brink of collapse and has led to significant gaps in immunization coverage. In response to these challenges, the Eastern Mediterranean Public Health Network (EMPHNET) organized two sessions during its Eighth Regional Conference in 2024. These sessions, “Public Health in Gaza: Priorities and Solutions” and “The War on Gaza: Challenges and Opportunities for the Health Sector,” gathered experts, policymakers, and healthcare professionals to discuss the immediate and long-term implications of the crisis and to call for action. Key areas of focus included emergency response planning, primary healthcare, communicable and non-communicable diseases, mental health support, and workforce capacity development. The discussions highlighted the urgent need for multi-sectoral collaboration and international support to address immediate healthcare needs and build a sustainable, resilient health system for Gaza. Recommendations included, first and foremost, ending the aggression, opening the borders, and stopping the illegal siege. Other recommendations included strengthening health governance structures, ensuring the protection of healthcare workers, and integrating innovative frameworks such as event- based disease surveillance and community-based mental health interventions. The sessions underscored the essential role of partnerships among local authorities, international organizations, and humanitarian agencies in fostering recovery and resilience. By prioritizing equity, resilience, and sustainability, the recommendations aim to guide efforts in rebuilding a functional and holistic healthcare system for Gaza’s future. The data and analysis presented reflect the status of Gaza’s public health system up to September 2024, based on insights shared during EMPHNET’s Eighth Regional Conference.